Antibacterial activities of medicinal plants of Nepal - Pokharel, K; Dhungana, BR; Tiwari, KB; Shahi, RB; Yadav, BK; Sharma, M; Shrestha, RK; Shrestha, D; Poudel, BH (Journal of Institute of Medicine Nepal, 2009)
Background: Medicinal plants of Nepal are still remaining to be assessed for their antimicrobial properties, which may lead to discovery of broad-spectrum antimicrobial compounds. Methods: Various parts of medicinal plants, viz. Acorus calamus, Curcuma longa, Emblica officinalis, Glycyrrhiza glabra (a non-indigenous to Nepal), Justicia adhatoda and Xanthoxylum armatum, were collected from hilly regions of Nepal. The plant parts were chopped into fine pieces, air-dried at 37°C for several hours, surface sterilized and grinded to powder. The antibacterial compounds were extracted by Soxhlet Reflux method and tested against common bacterial pathogens by agar well diffusion test. Result: All the crude extracts were found to be effective against Salmonella typhi, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Staphylococcus aureus. Among tested ones E. officinalis was found to the best antibacterial plant. Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) values of the crude extract of E. officinalis were found to be 8mg/ml and 16mg/ml respectively. Similarly, MIC value of A. calamus was 128mg/ml. Conclusion: Being highly effective against both Gram-positive and Gram-negative common bacterial pathogens, the antibacterial compounds from the plants can be exploited to commercial values provided in vivo assessment of the compounds are studied. Keywords: Antibacterial agents; medicinal plants; minimum inhibitory concentration; Nepal Journal of Institute of Medicine, August, 2008; 30:2 28-32 The full text of this paper is available from the Journal of Institute of Medicine website